2015
DOI: 10.1186/s12885-015-1593-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of brain metastasis with magnetic resonance imaging and stereotactic irradiation attenuated benefits of prophylactic cranial irradiation in patients with limited-stage small cell lung cancer

Abstract: BackgroundMagnetic resonance imaging (MRI) enables a more sensitive detection of brain metastasis and stereotactic irradiation (SRI) efficiently controls brain metastasis. In limited-stage small cell lung cancer (LS-SCLC), prophylactic cranial irradiation (PCI) in patients with good responses to initial treatment is recommended based on the survival benefit shown in previous clinical trials. However, none of these trials evaluated PCI effects using the management of brain metastasis with MRI or SRI. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…52 Furthermore, Ozawa et al deemed that PCI might be less effective in LS-SCLC provided extended management with cranial MRI and SRS were readily accessible. 53 PCI has thus been the topic of recurring discussion as experts have serially debated its pros and cons in particular in relation to potential neurologic sequelae. Historically, prior to the publication by Aupérin et al, Cmelak and colleagues published a large survey with a total of 1231 responders, 13 including 628 (51%) radiation oncologists, 587 (48%) medical oncologists.…”
Section: Prophylactic Cranial Irradiation In Ls-sclcmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Furthermore, Ozawa et al deemed that PCI might be less effective in LS-SCLC provided extended management with cranial MRI and SRS were readily accessible. 53 PCI has thus been the topic of recurring discussion as experts have serially debated its pros and cons in particular in relation to potential neurologic sequelae. Historically, prior to the publication by Aupérin et al, Cmelak and colleagues published a large survey with a total of 1231 responders, 13 including 628 (51%) radiation oncologists, 587 (48%) medical oncologists.…”
Section: Prophylactic Cranial Irradiation In Ls-sclcmentioning
confidence: 99%
“…Ozawa and colleagues postulated that PCI may be less effective in LS-SCLC provided extended management with brain MRI and SRS was readily accessible. 53 As previously extensively discussed, the landmark meta-analyses of PCI included trials in the pre-MRI era. Thus, critics have argued that its modest survival benefit might dissipate in the presence of comprehensive brain imaging as some have suggested that the improved survival outcome conferred by PCI may be attributed to treatment response of subclinical BM to cranial irradiation and not per se "PCI".…”
Section: Pci In Elderly (³70 Yr)mentioning
confidence: 99%
“…There are several reports but always with a very limited number of patients. In the series of Ozawa et al, patients had MRI just before PCI: 29 patients received PCI and 95 not (28). At 2 years the incidence of brain metastases was respectively 45.5% and 30.8% in the group with and without PCI; without any difference in survival.…”
Section: Limited Disease Sclcmentioning
confidence: 99%
“…Patients have to be prepared for hair loss, potentially with the help of psycho-oncologists, to minimise the impact on quality of life. When PCI is not implemented, close follow-up with cranial MRI should be performed if therapeutic radiotherapy would be an option [97].…”
Section: Prophylactic Cranial Irradiationmentioning
confidence: 99%